Open data driven public accountability. Issue 1 (20th March 2017) - Lourenço, Rui Pedro; Piotrowski, Suzanne; Ingrams, Alex
Abstract : Purpose: This paper aims to analyse extant literature on open data, distinguish and categorize the strands of public accountability research and use the results to provide better clarity in the concept of open data-driven public accountability. Design/methodology/approach: Systematic review of 135 open data articles and 155 accountability articles from the e-government reference library. A multi-stage analysis results in 12 articles which are categorized usingBovens' (2007) accountability theory of information, discussion and consequences. Conceptual development, using the literature analysis, forms the final section of the paper. Findings: Research demonstrates that a range of open data topics has been advanced. However, just 12 articles exist that simultaneously address open data and accountability theory. Of the total 155 public accountability articles, the preponderant focus is on the information ( N = 25) and discussion ( N = 7) stages of the accountability process. Just one article focuses on the complete accountability process. To address this problem, the characterization of open (government) data-driven public accountability establishes conceptual crispness and clarity. Originality/value: Public accountability theory on open government has become overshadowed by social and economic value perspectives. This paper clarifies and advances the open data-driven public accountability perspective. It takes stock of public accountability research, delimits the key issues and questions and highlights the next steps needed for developing scholarship.